2020
DOI: 10.1055/s-0040-1702199
|View full text |Cite
|
Sign up to set email alerts
|

Volar Scaphoid Plating for Nonunion: A Multicenter Case Series Study

Abstract: Background The volar scaphoid plate from Medartis (Medartis AG, Austrasse, Basel, Switzerland) is a variable angle titanium locking plate, preformed for the volar aspect of the scaphoid. It does not have compressive capability, and may act as a bridging device. It may provide an advantage over a compression screw where the pathoanatomy is less favorable to such a device with increased rotational stability. It may act as a buttress plate for correction of humpback deformity for example. It has been used in nonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
3
2
Order By: Relevance
“…Our result showed that a 100% union rate was achieved with scaphoid plating. The result of the union was consistent with the literature, more than 90% [ 5 , 14 - 16 ]. A systemic review by Morgan et al showed that scaphoid plating union rate 72-100% which included nonunion and trauma groups [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our result showed that a 100% union rate was achieved with scaphoid plating. The result of the union was consistent with the literature, more than 90% [ 5 , 14 - 16 ]. A systemic review by Morgan et al showed that scaphoid plating union rate 72-100% which included nonunion and trauma groups [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…The mean motion arc in our study was 105° whereas in other studies was 94°(Feliu et al), 104° (Mehling et al), 120° (Dodds et al), 115° (Eng et al), and 177° (Leixnering et al) [ 5 , 8 , 16 , 18 , 19 ]. In a systematic review of a few articles, the mean was 119° [ 19 ].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…21 Scaphoid plates also act as a buttress plate for correcting humpback deformity and may also provide additional rotational stability compared with screws. 22…”
Section: Discussionmentioning
confidence: 99%
“…21 Scaphoid plates also act as a buttress plate for correcting humpback deformity and may also provide additional rotational stability compared with screws. 22 Several papers have also described the use of scaphoid plating particularly as a salvage procedure for difficult scaphoid nonunions and after failed attempts with compression screw fixation. [11][12][13][14][15]23 Ghoneim et al demonstrated volar plating of scaphoid nonunion using straight and L-plates achieving union in 93% of their 14 cases.…”
Section: Smentioning
confidence: 99%